The Implementation of Cooperative Script Technique in Teaching Reading Comprehension to the Students of Senior High School - Pertiwi, Ananda Dian (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2017)
This research was intended to investigate whether the cooperative script technique is effective to improve reading comprehension ability to thetenth grade students of senior high school.This research focus on narrative text as the material and the tenth grade students of SMAN 1 Larangan, Brebes in academic year 2015/2016.This research was using quantitative method , with the pre-test post-test control as the design of the research. A group consisting of  30  tenth  graders  was taught using cooperative script as the technique and another group consisting of 30 tenth graders represented the control group. A pre and post test was applied  on both  groups. The quantitative data were taken from result of those achievement tests done. After  being  collected,  the  data  were analyzed using t-test formula. The study findings indicated that there are statistically significant differences at (α ≥ 0.05) in reading skills  among  the  mean  scores  of  the  control  group  and  the  experimental  groups  in  favor  of  the experimental groups. The result indicated that that the improvement of the scores in experimental group were influenced by two important things which can be found during cooperative script technique implementation. First, student reading ability was influenced by  retelling and working memory activity. Then, the students reading ability was influenced by the student motivation in reading. At last, The results suggest that cooperative script could be a potentially useful technique in teaching reading for ESL learners.Keywords: Reading Comprehension, Narrative text, Cooperative learning method, Cooperative script technique